Practical Analysis of Target Trial Emulation for Cardiorenal Outcomes in the Multimorbid Population - Luo, Yafei (International Journal of Public Health and Medical Research, 2026)
The comorbidity of cardiovascular and metabolic diseases is particularly common among middle-aged and elderly people. Traditional randomized controlled trials have strict inclusion criteria and often exclude subjects with multiple comorbidities, making it difficult for the research conclusions to reflect real clinical practice. This study performed target trial emulation, and selected chronic kidney disease, hypertension, Type 2 diabetes mellitus (T2DM) and heart failure comorbidity groups as the research object. Referring to the domestic CK-NET kidney disease monitoring database, combined with open data from two international cardiorenal trials (CREDENCE, DAPA-CKD), we compared the performance of traditional parallel control, basket test and platform test, and also analyzed the application of single endpoint, composite endpoint and hierarchical outcome indicators in this group of people. A clinically adaptable trial design reduces the required sample size and improves the detection of cardiorenal adverse events. The hierarchical composite endpoint is more suitable for evaluating the prognosis of patients with multimorbidity. This study can provide practical reference for the design of clinical trials and screening of indicators for cardiorenal multimorbidity.